Self-reported sexual orientation among undergraduates of 10 universities in Guangzhou, China - Yan, Yuan; Xiao, Shuiyuan; Liu, Haihong; Chue, Pierre (PloS one, 2018)
Few studies have investigated the distribution of sexual orientation among Chinese university students and identified the socio-demographic factors associated with sexual orientation. For the present study, we administered a paper-based, 5-point, self-report, sexual orientation scale to a stratified, random sample of 9071 undergraduates across all 10 universities in Guangzhou Higher Education Mega Center, Guangzhou, China. Multivariable ordinal regression analysis was used to explore the relationship between demographic factors and sexual orientation. A total of 8320 respondents completed the survey. Of 8182 valid respondents, 80.6% self-reported as exclusively heterosexual, 12.6% self-reported as mostly heterosexual, 5.4% self-reported as bisexual, 0.7% self-reported as mostly homosexual, and 0.8% self-reported as exclusively homosexual. About one fifth of male students and one fourth of female students reported some degree of divergence from exclusive heterosexuality. This indicates that in China there are a large number of university students who are potentially involved in same-sex sexual attraction.